Antioxidant and Antimycotic Activities of Two Native Lavandula Species from Portugal. (1st April 2015) - Baptista, Rafael; Madureira, Ana Margarida; Jorge, Rita; Adão, Rita; Duarte, Aida; Duarte, Noélia; Lopes, Maria Manuel; Teixeira, Generosa
Abstract : The antioxidant and antimycotic activities of the essential oils and extracts of two native Portuguese Lavandula species, L. stoechas subsp. luisieri and L. pedunculata, were evaluated by in vitro assays. The total phenolics and flavonoids content were also determined. The antioxidant potential was assessed through DPPH radical scavenging, inhibition of lipid peroxidation (ILP), and DNA protection assays. All samples displayed a high DPPH scavenging activity, some of them showing concentration dependence. The majority of the samples were also able to inhibit lipid peroxidation. A strong correlation was observed between the results of DPPH and ILP assays and the flavonoids content of the samples. In the DNA protection assay, all the extracts were able to preserve DNA integrity. The antimycotic activity was performed against twelve fungi belonging to Basidiomycota and Ascomycota Divisions. L. stoechas subsp. luisieri exhibited the broadest activity spectra. L. pedunculata extracts were active against five fungi. Cryptococcus neoformans was the most sensitive, being inhibited by all the extracts. Our results led to the conclusion that L. stoechas subsp. luisieri and L. pedunculata can be useful as new sources of natural antioxidants and antimycotic agents, providing a possible valorization of the existing biodiversity and resources of Portuguese flora.